Pandemic, Exception and the Law: Notes on the Shattered Nomos of Europe - Cercel, Cosmin (Acta Universitatis Lodziensis. Folia Iuridica, 2021)
In this article I propose a critical evaluation of the current European politico-legal landscape that unfolds under the conditions of the COVID-19 pandemic. My aim is to offer an analysis of the symbolic status of legality in this context and to reflect on its historical trajectory, by introducing it in a longer historical timescale than usually proposed as well as by insisting on the specific nexus between emergency legislation and authoritarian ideologies within Europe. In doing so I propose a new genealogy of the state of exception apt to articulate the relationship between the force of law, legal normativity, and ideology in modern capitalism. The thesis that I defend here is a simple one: the ongoing pandemic has operated a historical acceleration that the law, understood here as medium that articulates power symbolically in a public and ostensible manner, is not able to catch up with. To substantiate this thesis, I venture first to take stock of the existing theories, analyses and narratives on the relation between the pandemic and the politico-legal landscape of Europe. In doing so I shall focus first on traditional constitutional law accounts and on Italian philosopher Giorgio Agamben’s criticism of the legal responses to the pandemic. Following this analysis, I move towards a situation of the pandemic within the sphere of the multiple crises befalling Europe that have become visible since 2015. At this stage I draw attention to the manifold layers of emergency legality and states of exception that have been sapping the liberal democratic nomos putatively defended within Europe. In a third move, I embark on a synoptical clarification of the relationship between law, ideology and the history of class struggle. In a fourth and last intervention I intend to assess the current nexus between the pandemic, exception and the law as a specific form of dissolution of the liberal nomos.